‘Charm is deceitful, and beauty is vain; but a woman who fears Yahweh, she shall be praised. Funeral celebrations of Teresa and Paulina Wielopolska née Potocka - Staniszewska, Aleksandra (Requiem, 2025)
The aim of the article is to present the funeral ceremonies of Aleksander Wielopolski’s wives – Teresa and Paulina Wielopolska née Potocka. Although these ceremonies are over 60 years apart, and both took place in different political conditions (Teresa died in February 1831 – during the November Uprising, and Paulina in 1895), as well as different family situations (Teresa died as a young married woman, and Paulina as an 82-year-old widow), many features can be seen that connect the funerals of the wife of the Pińczów mayor. The findings presented in the article are based on archival materials, including correspondence of family members about the organization of both funerals, bills, and press articles.